2018
DOI: 10.1080/20469047.2018.1489628
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use in the management of children with the common cold at a provincial hospital in Papua New Guinea: a point-prevalence study

Abstract: Although among healthcare workers, there was a gap between knowledge of aetiology and knowledge of appropriate management of the common cold, there was a larger apparent gap between that knowledge and practice. Findings from this study could be used to identify interventions promoting rational antibiotic use, targeting both health-care workers and the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…Iz raziskav je razvidno, da starši ob pojavu okužb zgornjih dihalnih poti velikokrat uporabljajo homeopatska zdravila (Fixen, 2018), paracetamol (Bham et al, 2016), domača zdravila, manj pa sledijo navodilom članov negovalnega in zdravstvenega tima (Kumar et al, 2011). Starše je treba informirati, kdaj z otrokom k zdravniku in kdaj otrok resnično potrebuje antibiotik (Raft et al, 2017), saj ga mnogim zdravniki predpišejo pogosto in prehitro (Alexandrino et al, 2016;Dekker et al, 2017;Tyrstrup et al, 2017;Zamunu et al, 2018;Long et al, 2019).…”
Section: Diskusijaunclassified
See 1 more Smart Citation
“…Iz raziskav je razvidno, da starši ob pojavu okužb zgornjih dihalnih poti velikokrat uporabljajo homeopatska zdravila (Fixen, 2018), paracetamol (Bham et al, 2016), domača zdravila, manj pa sledijo navodilom članov negovalnega in zdravstvenega tima (Kumar et al, 2011). Starše je treba informirati, kdaj z otrokom k zdravniku in kdaj otrok resnično potrebuje antibiotik (Raft et al, 2017), saj ga mnogim zdravniki predpišejo pogosto in prehitro (Alexandrino et al, 2016;Dekker et al, 2017;Tyrstrup et al, 2017;Zamunu et al, 2018;Long et al, 2019).…”
Section: Diskusijaunclassified
“…Alzahrani et al (2018) ocenjujejo, da je treba opredeliti dejavnike oziroma pripraviti smernice, na osnovi katerih bi otroku z okužbo zgornjih dihalnih poti utemeljeno predpisali širokospektralni antibiotik. Zdravstveni delavci zato nujno potrebujejo strokovna izobraževanja o etiologiji in obvladovanju okužb zgornjih dihalnih poti pri otrocih (O'Connor et al, 2018), starši pa zdravstveno vzgojo o pravilni in racionalni uporabi antibiotikov (Zamunu et al, 2018). Zdravstveni delavci na pediatričnih oddelkih morajo staršem podati razumljiva navodila o pravilni in smotrni uporabi antibiotikov (Lunze et al, 2017).…”
Section: Raven Dokaza / Level Of Evidenceunclassified
“…31 High rates of unnecessary prescribing was also confirmed in a recent paediatric outpatient study in PNG: 82% of children presenting with a common cold were given antimicrobials. 32 Human movement and travel Traditionally, PICTs experienced low volumes of airline traffic due to their geographical dispersion, small populations and high costs of fuel and parts. However, the recent emergence of low-cost carriers has led to greater capacity on existing airline routes and the introduction of new routes.…”
Section: Community and Prescriber Understanding Of Amrmentioning
confidence: 99%
“…(10)(11)(12)(13)(14)(15)(16)(17)(18) These drug resistant strains have become global health crises and an emergency. Factors associated with antibiotic use are both community and hospitals based as studies have reported increased use of antibiotics by parents and caregivers as well as health care providers ( (19)(20)(21)(22)(23)(24)(25). It is therefore imperative to monitor and control antibiotic prescribing to ensure judicious use, prevent resistance and reduce cost of healthcare.…”
Section: Introductionmentioning
confidence: 99%